The English Language Learning Experiences and Career Positioning of Teacher Luz Marina (2021)
This narrative research study presents an exploration of the experiences of Luz Marina; a middle school English teacher from Cúcuta, focusing on the impact suffered during the first years of her teaching, caused by struggles with her English language acquisition. Additionally, this narrative study discloses the emotional and ethical motivations this teacher had, in order to go in the to look out for extracurricular English proficiency instruction, which provided her with the needed language training to overcome her limited communicational abilities as well as nourished her with knowledge about international cultures, considering the importance of the sociolinguistic aspect in the English as a foreign language teaching practice.